2012
DOI: 10.1210/jc.2011-2817
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Recurrence and Long-Term Morbidity in Craniopharyngioma: A Systematic Analysis of 171 Patients

Abstract: Craniopharyngioma continues to be associated with severe outcomes. Higher morbidity rates are found in patients with early-onset disease (before 10 yr), initial SIHT, or in whom pterional surgery was required. Markers of recurrence are difficult to identify, with SIHT being the most powerful predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 36 publications
9
82
3
Order By: Relevance
“…It has been clearly shown that children rarely have the papillary type tumor. Gautier reported that 61 children had the adamantinomatous type tumors compared with only 3 other children with the papillary type ones [2]. In our study, none of the children had the papillary type tumor.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…It has been clearly shown that children rarely have the papillary type tumor. Gautier reported that 61 children had the adamantinomatous type tumors compared with only 3 other children with the papillary type ones [2]. In our study, none of the children had the papillary type tumor.…”
Section: Discussioncontrasting
confidence: 51%
“…An important finding of our study was that children had more frequent post-operative complication of diabetes insipidus than adults. Gautier et al found that patients with early onset disease (age <10 years) had a significantly higher morbidity rate [2]. Lower awareness of increased intracranial pressure (IICP) might facilitate the brain tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…HI of CP has been reported as a major risk factor to impairment of long-term survival (7,8,14) and quality of life (8,21,22,23,24,25,26,27,28,29,30) in CP patients. The question of whether DOH before diagnosisspecifically whether prolonged interval between the first appearance of symptoms and the time of diagnosiscontributes to adverse sequelae and impaired survival had not been answered before this study.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has also been seen in other studies but is limited in our analysis due to small sample size and a variety of characteristics that reflect treatment decisions. 14 Residual symptoms are also expected to have an impact in QOL. Both long-term visual deficits and endocrine deficits were associated with decreased QOL.…”
Section: Predictors Of Increased or Decreased Postoperative Qolmentioning
confidence: 99%